The Economic Order Quantity Repair and Waste Disposal Model: Solution Approaches - Billah, Misha; Rizvia, MM; Das, Lipon Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2021)
As an inventory management instrument, Economic Order Quantity (EOQ) is gaining increased attention. EOQ has become the focus point of everyone’s interest, especially scientists. There are inventory problems in the production and repair system where the used products are collected to repair, and after repairing, it is considered as a new product. A two-stage EOQ model for manufacturing, repairing and disposing of products is discussed in our analysis. The present model follows a former model introduced by Nahimas and Rivera, where the repair system is finite. We propose a new mathematical model in reverse logistics system where demand in production and repair items follows an exponential rate. Mathematical expressions for determining the production and repair quantities are also initiated here. In this model, it is assumed that the available space for supply and repair depots is limited, and we impose two constraints that turn the problem into a constrained optimization model. We also conduct extensive numerical experiments, and advantages are addressed. GANIT J. Bangladesh Math. Soc. 40.2 (2020) 134-144